Carbohydrate supplementation fails to improve the sprint performance of female cyclists - Jarvis, A. T.; Felix, S. D.; Sims, S.; Jones, M. T.; Coughlin, M. A.; Headley, S. A. (Journal of Exercise Physiology online, 1999)
This study was designed to examine the effect of a 7% carbohydrate electrolyte beverage (CE) on the sprint performance of trained female cyclists immediately following 50 min of cycle ergometry at 80% VO2 max. The Wingate Anaerobic Power Test (WAT) was used to measure peak power, mean power, minimum power, and rate of fatigue. No significant (p > .05) differences were found between the CE and placebo (PL) treatments for any WAT indices. Blood glucose was found to be significantly higher (p < .05) toward the end of the time trial for the CE group than for the PL group. RPE increased more dramatically from baseline for the PL group than for the CE group (p < .05). The results suggest that high intensity exercise performance of female cyclists is not improved with the consumption of a CE beverage during exercise despite a reduced perception of effort.